Analyzing barriers for implementing new vehicle scrap policy in India. (January 2023) - James, Ajith Tom; Asjad, Mohammad; Kumar, Girish; Chandra Shukla, Vipin; Arya, Vedpal
Abstract: Developed countries have already implemented a vehicle scrap policy that prevents the on-road usage of old vehicles beyond a certain age to curtail pollution. Recently Indian government also announced its plans and policies for vehicle scraping. There is a multitude of barriers to the implementation of such a policy in India. This paper identifies and models all implementation barriers. Literature review and interactions with various stakeholders helped to identify the barriers. The identified barriers are processed with a hybrid methodology, which is a combination of the Fuzzy Analytic Hierarchy process and the Decision-Making Trial and Evaluation Laboratory. The data is modeled in a fuzzy context to account for issues of ambiguity and subjectivity. This study helps policymakers and other stakeholders by identifying the barriers to vehicle scrap policy implementation in India. Furthermore, this paper offers insights for future research in developing policies and practices for India's emerging vehicle scrap business.